Assessment of specificity of the badcamp agility test for badminton players - de Franca Bahia Loureiro Jr, L.; Oliveira Costa Dias, M.; Couto Cremasco, F.; Guimaraes da Silva, M.; Barbosa de Freitas, P. (Journal of Human Kinetics, 2017)
The Badcamp agility test was created to evaluate agility of badminton players. The Badcamp is a valid and reliable test, however, a doubt about the need for the use of this test exists as simpler tests could provide similar information about agility in badminton players. Thus, the aim of this study was to examine the specificity of the Badcamp, comparing the performance of badminton players and athletes from other sports in the Badcamp and the shuttle run agility test (SRAT). Sixty-four young male and female athletes aged between 14 and 16 years participated in the study. They were divided into 4 groups of 16 according to their sport practices: badminton, tennis, team sport (basketball and volleyball), and track and field. We compared the groups in both tests, the Badcamp and SRAT. The results revealed that the group of badminton players was faster compared to all other groups in the Badcamp. However, in the SRAT there were no differences among groups composed of athletes from open skill sports (e.g., badminton, tennis, and team sports), and a considerable reduction of the difference between badminton players and track and field athletes. Thus, we concluded that the Badcamp test is a specific agility test for badminton players and should be considered in evaluating athletes of this sport modality.